Diatom metabarcoding vs. morphology in monitoring freshwater and saline lakes in Serbia - Vlaović, Ljubica; Lemonnier, Clarisse; Alric, Benjamin; Rimet, Frédéric; Ćirić, Miloš; Miletić, Srđan; Milovanović, Željka; Petrović, Vladimir; Vidaković, Danijela (Frontiers in Ecology and Evolution, 2025)
IntroductionDiatoms are among the most widely used indicators for assessing ecological conditions in aquatic habitats, yet traditional microscopy remains time-consuming and taxonomically demanding. This study explores the potential of rbcL-based DNA metabarcoding as an alternative or complement to morphological analysis for monitoring both freshwater and saline lakes. MethodsWe investigated diatom assemblages in two artificial freshwater lakes and two inland saline lakes in Serbia by comparing species composition, diversity, and ecological index performance across both methods.Results and discussionA total of 227 taxa were detected by metabarcoding and 212 by microscopy, with both approaches consistently showing higher richness and Shannon diversity in freshwater than in saline lakes. Redundancy analysis revealed conductivity and salinity as the main drivers of community structure, clearly separating freshwater from saline systems, while co-inertia analysis demonstrated strong agreement between the two methods. In freshwater lakes, diatom index values derived from microscopy and metabarcoding showed partial to good agreement, with IPS and IBD emerging as the most consistent and reliable indices across methods. The DISP and TBI indices, initially developed for soda lakes, were applied here for the first time using metabarcoding data. However, their application was limited by incomplete reference databases, missing trait assignments, and lower taxonomic coverage, reducing the reliability of index-based evaluations in these habitats. Overall, while metabarcoding demonstrated strong potential --particularly in freshwater systems --a combined morphological and molecular approach offers a more comprehensive and reliable assessment across complex environments like inland saline lakes. This study contributes new sequence data to open-access diat.barcode databases, supporting the wider adoption of DNA-based tools in aquatic biomonitoring.